Dose-dependent anticholesterol effects of Fuji apple simplicia in a rat model of metabolic syndrome - Himawan Pramudana Amiruddin; R. Prihandjojo Andri Putranto; Amalina Shabrina; Veronika Ika Budiastuti (Indonesian Society for Biochemistry and Molecular Biology, 2026)
Background: Metabolic syndrome-associated dyslipidemia increases cardiovascular disease risk. Fuji apples (Malus domestica) contain bioactive compounds that may modulate cholesterol metabolism. Objective: To evaluate dose-dependent anticholesterol effects of Fuji apple simplicia in metabolic syndrome rats. Methods: Thirty male Wistar rats were allocated into five groups (n=6): negative control, positive control (metabolic syndrome without treatment), and three treatment groups receiving simplicia at 150, 300, or 450 mg/200 g body weight/day for 28 days. Metabolic syndrome was induced using high-fat diet and streptozotocin-nicotinamide injection. Total cholesterol was measured using enzymatic colorimetric assay and analyzed using mixed ANOVA. Results: Simplicia produced significant dose-dependent cholesterol reductions compared to positive control (p<0.001). Reductions were 71.77 mg/dL (34.09%), 100.53 mg/dL (47.78%), and 112.02 mg/dL (52.75%) at doses of 150, 300, and 450 mg/200 g body weight/day, respectively. Conclusion: Fuji apple simplicia exhibits significant anticholesterol activity in metabolic syndrome rats through a dose-dependent mechanism, supporting its potential as a complementary intervention for hypercholesterolemia management in metabolic syndrome.